Penerapan Undang-Undang Perlindungan Perempuan dalam Kasus Kekerasan dalam Rumah Tangga - Agustin, Reza (Proceedings Series on Social Sciences & Humanities, 2024)
The phenomenon of cases of domestic violence (hereinafter referred to as domestic violence) is currently increasing, in terms of quantity and quality. This phenomenon is a serious concern and requires all parties to understand all forms of crime and the factors that cause it, as well as efforts to overcome domestic violence. The forms of domestic violence that occur vary greatly, such as physical, psychological, sexual violence and violence in the form of neglect. These various forms of crime are crimes that are prohibited and punishable as regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence (hereinafter referred to as the PKDRT Law) which aims to ensure that victims of domestic violence, especially women, receive legal protection.